Investigation of Solubility of Radioactive Elements Contained in Ashes of Yatagan Thermal Power Plant in Acetic Acid - Kursun, I.; Terzi, M. (Asian Journal of Chemistry, 2015)
Coal combustion residuals consist of 90 % of all fossil fuel combustion residuals generated across the world. Million tons of fly ashes are generated on a yearly basis. For now, only 20 % of such fly ashes can be utilized and the remaining amount is used for land filling purposes or deposited in surface impoundments. The most important waste material in modern thermal power plants is very fine ash particles generated through the combustion of powder coals and spread by flue gases. About 110 g ashes release as a waste material in the generation of 1 kWh energy by a thermal power plant. Approximately 650.000 tons of fly ashes and bottom ashes are obtained from a power plant with the capacity of 1000 MW. Such toxic trace elements as arsenic, cadmium, lead, antimony, selenium, tin, molybdenum and zinc are transferred to wastes upon the combustion of lignite coals. Toxic trace elements contained in fly ashes can sweep even into surface and underground waters as a result of the contact of ash with water under suitable atmospheric conditions due to improper storage of the ashes. Furthermore, there are many studies conducted in terms of the recovery of precious metals and radioactive minerals in fly ashes. Such studies are important both for economical purposes and environmental pollution. Within the scope of this study, a series of characterization studies then leaching tests were carried out on the samples of fly ashes taken from a thermal power plant operated in Turkey. In order the ashes to be evaluated, the leaching of the samples and the optimum leach parameters were investigated with the use of acetic acid. Finally, opportunities for the recovery of uranium and thorium from the ashes were addressed.